Shopee” Advertisement: A Dream Beyond Reality - Rahmawati, Risma Nur (LPPM Universitas Pekalongan, 2022)
Shopee claims that during QS-2020 there were 260 million transactions on the Shopee platform with an average daily rate of 2.8 million transactions. This indicates that shopee is one of the e-commerce that is in demand by the people of Indonesia. The product in this case is only a commodity that fulfills hopes, dreams, desires to show self-existence. Shopee offers everything that humans need from genuine to imitation goods. Based on the results of the analysis of the two problem formulations above, it can be concluded that Shopee is an application that is in demand by many people because it offers free shipping on beautiful dates. In addition, shopee also carries an orange color brand that is easy for the public to remember. Advertising is one of the important factors in influencing the culture of consumerism in society.